HIV Knowledge and Perceived Risk Among Black Men and Women Who Are Incarcerated in Kentucky. Issue 3 (May 2023) - Thorpe, S.; Miller-Roenigk, B.; Hargons, C. N.; Dogan, J. N.; Thrasher, S.; Wheeler, P.; Oser, C.; Stevens-Watkins, D.
In the United States, Black men and women who are incarcerated bear a disproportionate and inequitable burden of HIV infection. While HIV knowledge does not consistently predict HIV risk behaviors, HIV knowledge can inform one's perceptions of their risk for HIV. We examined gender differences in HIV knowledge and perceived risk of contracting HIV ( N = 424) among Black men and women who were incarcerated and nearing community reentry from seven prisons in Kentucky. Our results demonstrated that women reported greater levels of HIV knowledge and perceived greater risk for contracting HIV than their male counterparts. Implications for HIV prevention interventions are discussed.